Electronic structure and optical property of p-type Zn-doped SnO2 with Sn vacancy - 孙桂鹏 闫金良 牛培江 孟德兰 (半导体学报：英文版, 2016)
The electronic structures and optical properties of intrinsic SnO2, Zn-doped SnO2, SnO2 with Sn va- cancy （Vsn） and Zn-doped SnO2 with Sn vacancy are explored by using first-principles calculations. Zn-doped SnO2 is a p-type semiconductor material, whose Fermi level shifts into the valence band when Zn atoms substitute Sn atoms, and the unoccupied states on the top of the valence band come from Zn 3d and O 2p states. Sn vacancies increase the relative hole number of Zn-doped SnO2, which results in a possible increase in the conductivity of Zn-doped SnO2. The Zn-doped SnO2 shows distinct visible light absorption, the increased absorption can be seen apparently with the presence of Sn vacancies in the crystal, and the blue-shift of optical spectra can be observed.